2016
DOI: 10.1037/edu0000107
|View full text |Cite
|
Sign up to set email alerts
|

Achievement gaps for students with disabilities: Stable, widening, or narrowing on a state-wide reading comprehension test?

Abstract: Reading comprehension growth trajectories from 3rd to 7th grade were estimated for 99,919 students on a state reading comprehension assessment. We examined whether differences between students in general education (GE) and groups of students identified as exceptional learners were best characterized as stable, widening, or narrowing. The groups included students with disabilities (SWD) from 8 exceptionality groups and 2 groups of academically gifted students (AG). Initial reading comprehension achievement diff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
42
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(48 citation statements)
references
References 66 publications
1
42
0
1
Order By: Relevance
“…This phenomenon is most likely due to changes in the reading task over time. In earlier grades, text complexity is limited; constrained word-level skills are highly predictive of reading comprehension (Schulte et al, 2016). In later grades, the broader constructs of language and background knowledge are increasingly predictive of reading comprehension (Ahmed et al, 2016; Catts, Adlof, & Weismer, 2006).…”
Section: Discussionmentioning
confidence: 99%
“…This phenomenon is most likely due to changes in the reading task over time. In earlier grades, text complexity is limited; constrained word-level skills are highly predictive of reading comprehension (Schulte et al, 2016). In later grades, the broader constructs of language and background knowledge are increasingly predictive of reading comprehension (Ahmed et al, 2016; Catts, Adlof, & Weismer, 2006).…”
Section: Discussionmentioning
confidence: 99%
“…Problems with sentence-level reading were also apparent among German-reading students, especially those classed in Profiles 1 (poor readers) and 2 (below-average readers), and very little reading improvement was seen after the first grade. The same negative reading comprehension growth pattern was established in a study of students in third through seventh grades that was conducted by Schulte, Stevens, Elliott, Tindal, and Nese (2016), and again in a study of children aged 7 through 17 that was conducted by Wei, Blackorby, and Schiller (2011). Both studies concluded that the developmental reading comprehension course for students with disabilities can be defined as a deficit model, in which the initial differences in skill levels persist over time with no sign of lower-achieving groups catching up to higher-achieving groups.…”
Section: Discussionmentioning
confidence: 59%
“…Many studies have examined reading growth over time, investigating why some students succeed and others fail in reading by the time they get to middle school. In particular, research has identified certain subgroups of students that tend to lag behind in reading: students from lower socioeconomic households (Luyten & Bruggencate, 2011;McCoach, O'Connell, Reis, & Levitt, 2006;Morgan, Farkas, & Hibel, 2008;Morgan, Farkas, & Wu, 2011), students who are speech and language impaired (Farkas, 2011), students with other learning disabilities (Schulte, Stevens, Elliott, Tindal, & Nese, 2016;Wei, Blackorby, & Schiller, 2011), and language-minority students with limited English proficiency (Kieffer, 2008(Kieffer, , 2011Nakamoto, Lindsey, & Manis, 2007). Other longitudinal research has focused less on child characteristics and more on the contributions of specific components of literacy to reading comprehension.…”
Section: Longitudinal and Cross-sectional Quantitative Findingsmentioning
confidence: 99%